(3aj CMhGdfG hCMhGd ShGfG(B/ s - (3UGZjI, MGRes ((3dHfGf;s (3GdSGbj;s, 2023)
The book discusses two main concerns. Firstly, addresses the Eurocentric criticism and emphasizing the need to understand various aspects of the complex Western experience. Secondly, it highlights the significance of the 'Arab National Liberation Movement' in shaping the current situation in the Arab East. The text underscores the connection between contemporary tragedies and the movement's historical triumph, particularly through military coups, portraying these struggles as ongoing efforts for freedom, sustenance, and human dignity.
(3jJfGhd Hjf UaMGJg gnqejf GKnfjf, GdCqhd bjGS ChVGYfG ceMdjjf Ydi TQhW JbqOe GdZQH, MjK jbhd UGZqjI(B: (S0(3fYde Cqf JgeI GdeQcRjI GdChQhHjI Ch GdZQHqjI gj OGFekG HGdeQUGO deKd gPg GdebGQHGJ, dgPG HOG ef GdVQhQj GdJYQja HHYV ChLg GdUjQhQI GdZQHjI PGJ GdefGd GdUYH, EP WZi JbdjOqjkG EqeG GNJRGd JGQjN GdZQH hcdGSjcqjGJg hEqeG EZaGdg(S1(B. (3CqeG Gdgqe GdKGfj aJUag ebqOeI GdcJGH HCfg (S0(3GYJHGQ eG HGJ ojYQa H`(S1(3MQcI GdJMqQQ GdhWfqj GdYQHqjI(S1 (3MqOkG aGUdkG hMGSekG aj JbQjQqjJg, hef Kqe GdQHW Hjf GdeBSj GdQGgfI aj GdeTQb GdYQHj hJdc GdMQcI aj XaQgG hUYhOgG ef NdGd GdEfbdGH GdYScQj, gj GdJj dG jRGd ojQLe HbGehSgG hHNQGaGJgG cqd LgmO aj WdH GdMQjI hGdNHR hGdcQGeI GdEfSGfjI(S1(B.s
Title translation: In our circumstances and the circumstances of others- Author: Hazem Saghieh
Arabic
Keywords: Contemporary (1990 onwards); Islamic renewal -- Arab countries; JA71-80-Theory. Relations to other subjects; Liberalism -- Arab countries; Arab World